Pemanfaatan Aplikasi KePO sebagai Strategi Deteksi Dini Kanker Payudara - Novitarum, Lilis; Ginting, Arjuna; Sitepu, Aprilita Br. (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Breast cancer is the second highest cause of death in the world. However, cancer can be prevented with a healthy lifestyle, even breast cancer that is detected early and treated immediately increases the patient's life expectancy. The Online Breast Cancer Application (KePO) contains information on calculating breast cancer risk scores, material on avoiding breast cancer risk factors and how to do breast self-examination. This study used a descriptive design which aimed to measure the use of the Kepo application as an early detection strategy for breast cancer with a sample size of 26 people. Based on the research results, respondents stated that KePO is beneficial for society. 34.6% of respondents strongly agreed that by using the KePO application I could quickly understand breast self-examination techniques, 38.5% of respondents strongly agreed that by using the KePO application I did not need to pay for transportation to go to a health facility, 38.5% of respondents stated that they strongly agree that by using the KePO application I do not feel embarrassed about doing my own breast examination, 42.3% of respondents stated that they strongly agree that using the KePO application helps save time queuing at health facilities and 34.6% of respondents stated that they strongly agree that the KePO Application very useful. The KePO application has a positive impact and is easy to use by women of childbearing age, so it tends to be a leverage to reduce breast cancer rates in the future.